Hypotheses on "Women’s writing and hispanic culture" - Reisz, Susana (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Theoretical in approach and grounded in literary history, this paper proposes a discussion of the controversy surrounding the category "écriture féminine" and how this category reveals itself in the literary production of both Spanish America and Spain in the eighties and nineties. Far from encompassing each and every text written by women authors, the object of investigation here is restricted to the type of literary practice that successfully articulates both the ways of experiencing and the marginal condition specifically attached to the "féminine" gender role. The author argues that the representational techniques and discoursive strategies of "femininity" -as well as the marginal condition they expose- are subject to variation in a manner similar to literary trends. She contends also that in the Spanish-speaking world rapid changes of a rather homogeneous nature are taking place.